PUBLIC-PRIVATE PARTNERSHIP AS THE STIMULATING DEVICE FOR HUMAN CAPITAL DEVELOPMENT - Tereshchenko , Dina (Theory and Practice of Public Administration, 2020)
The article is concerned with research of the possibility of use of public- private partnership as the stimulation device for human capital development in Ukraine. Achieving of sustainable development goals involves the realization by the government of socially important tasks, which require corresponding financial resources. Reforming of the social service system, the necessity for additional financial and technological resources, practical implementation of information technologies have established an effective cooperation model between government and business on the base of public-private partnership (PPP) mechanisms. PPP mechanisms influence on human capital development due to implementation of the projects in the spheres of education, science and public health service, providing economic and social results. The problematic that exists in educational and medical spheres today enforces the necessity in usage of PPP that should become an important element in development of strategic modernization of the projects of the corresponding social sectors.It is proved that the innovative part of PPP projects is important, that definitely requires involvement of highly-skilled professionals in the realization of innovative solutions. It is stated that such task involves training of specialists as per corresponding sectors by means of life-long learning education, retraining, international internship, continuing education; search and recruitment of staff of necessary qualification, training of professionals of government bodies for function execution as the government in the realization process of public-private partnership projects. In the case of successful implementation of PPP projects, the solution of important social and humanitarian problems of the society is provided, and hence, human development, improvement of life quality through the corresponding spheres: education, medicine, culture, environmental protection and others are affected. It is noted that the state should play a key part both as an organizer, as a coordinator and as an entity of cooperation in the system of state institutions, and civil society entities..